Revisi Pasal Perzinaan dalam Rancangan KUHP: Studi Masalah Perzinaan di Kota Padang dan Jakarta - Lidya Suryani Widayati (Jurnal Hukum IUS QUIA IUSTUM, 2009)
Sexual intercourse between men and women out of marital relationship indicates the current crisis of morality among people. More than this, the sexual intercourse among youths seems to be increasing as the increase of the cases of sexual transmitted diseases (STD). Considering this, the effort to overcome such deviation through criminalization policy cannot be delayed any longer, for the purpose of overcoming any possible negative impacts and deteriorate of people’s behavior.Keywords: penal code bill, Section on adultery